Amino‐Supported Palladium Catalyst for Chemo‐ and Stereoselective Domino Reactions. Issue 2 (10th November 2020) - Li, Man‐Bo; Yang, Jie; Yang, Ying; Xu, Guo‐Yong; Luo, Gen; Yang, Jianping; Bäckvall, Jan‐E.
Abstract: A solid amino‐supported palladium catalyst is used in an oxidative domino reaction for the diastereoselective construction of alkyne‐substituted cyclopentenol compounds. This heterogeneous catalyst exhibits high efficiency and excellent chemoselectivity, as well as good recyclability. The chemoselectivity of the domino reactions was readily controlled by switching the solvent and catalyst. Asymmetric syntheses and an oxidative carbocyclization‐borylation reaction have also been developed based on the heterogeneous palladium catalyst. Abstract : An oxidative domino reaction is developed here for the construction of alkyne‐substituted cyclopentenol compounds by using an amino‐supported Pd catalyst. The properties of the heterogeneous catalyst contribute to its high efficiency and excellent chemoselectivity, as well as good recyclability.